Entrepreneurship in Colombia with the new Simple Tax Regime and its social impact on business formalization - Hernandez Avella, Sally Julieth
The simple regime is intended to reduce tax burdens and promote entrepreneurship to formalize companies, guaranteeing compliance established in the tax statute. This article will demonstrate how the factors of the simple tax regime influence the creation and formalization of a company, as well as the development of entrepreneurship in Colombia. Through a mixed investigation with a triangular approach that brings together the documentary review and the application of surveys as an instrument of information collection, taking as samples merchants in the city of Bogotá, in the town of Engativá, specifically in the Quirigüa neighborhood. Currently, the investigation is in the information collection phase, with partial results, showing that some of the merchants interviewed are unaware of the benefits they would have by using the simple tax regime, they have not been formalized for fear of the costs that may be incurred. file, such as taxes and the time they can use to carry out procedures. In addition to this and taking into account that one of the requirements to belong to this regime is that of electronic invoicing, many have not yet carried it out, in the same way because it involves costs that are not contemplated.